Los hongos micorrizogenos arbusculares de la region de Nizanda, Oaxaca, Mexico - Guadarrama Chavez, P.=700 1 Camargo Ricalde, S.L.; Hernandez Cuevas, L.; Castillo Arguero, S.
(En, Es)
ilus., 36 ref.
Keywords: SIMBIOSIS; MAIZ; MICORRIZAS ARBUSCULARES; VESICULARES; COMPOSICION BOTANICA; VEGETACION; MEXICO